Leather Industry Business Linkages (Case Study in District Magetan) - Dilahur Dilahur (Universitas Muhammadiyah Surakarta, 2003)
Leather industry in Magetan covers two forms; they are tanning and leathercraft. During 1960 and 1970, the leather industry decreased in its production, but in 1990 Magetan becomes the center of leather industry. Its development appeals to be studied closely. The goals of this study are to know the relation between tanning and leathercraft, the connection between these industries and other economic ativities, and their connection with production factor. This study uses survey methhod. The respondents are taken proportionally from both of those leather industries. The data is obtained inetrviewing the respondents with questionnaire that related to the input and out put of the industry. The result of this study shows that there is no relationship between the kind of industries (small and household industry) and its capital, especially in its raw material (44,44%). The relationship between tanning and leathercraft is low, because it is only 24,2% input of leathercraft which taken from output of tanning. The region relationship for tanning is larger, because the products that are sold to other regions are 97,22% for tanning and 68,29% for leathercraft. Its relationship to other sectors especially for labour supply is 56,48% from farming and trade sectors in marketing.